India at the crossroads : sustaining growth and reducing poverty - Callen, Tim.; Reynolds, Patricia; Towe, Christopher M. (Washington, D.C. : International Monetary Fund, 2001)
The authors examine the numerous structural and policy changes Indian authorities have adopted since the 1991 balance of payments crisis; how these changes helped India weather the Asian financial crisis of 1997-98; the risks to fiscal sustainability and their implications for growth; the challenges facing monetary policy in the face of financial market liberalization; and the benefits of structural reform and fiscal policy for growth, poverty, and the reduction of regional disparities.
Includes bibliographical references.
oif 04/08/16
Loan
Keywords: Economic policy; Structural adjustment; Fiscal policy; Sustainable development; India